2018
DOI: 10.1186/s12929-018-0448-y
|View full text |Cite
|
Sign up to set email alerts
|

Acid-sensing ion channels: dual function proteins for chemo-sensing and mechano-sensing

Abstract: BackgroundAcid-sensing ion channels (ASICs) are a group of amiloride-sensitive ligand-gated ion channels belonging to the family of degenerin/epithelial sodium channels. ASICs are predominantly expressed in both the peripheral and central nervous system and have been characterized as potent proton sensors to detect extracellular acidification in the periphery and brain.Main bodyHere we review the recent studies focusing on the physiological roles of ASICs in the nervous system. As the major acid-sensing membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(133 citation statements)
references
References 136 publications
1
132
0
Order By: Relevance
“…The contribution of ASIC3 to nociceptive mechanotransduction under the physiological condition is a matter of debate (Cheng et al, ; Deval & Lingueglia, ; Lingueglia, ), whereas ASIC3 is reported to be involved in proprioceptive mechanotransduction (Lin et al, ). In the present study, a selective blocker of ASIC3 administered to the naïve muscle via intramuscular injection did not alter the mechanical withdrawal threshold, indicating that ASIC3 played no role in the normal mechanical pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The contribution of ASIC3 to nociceptive mechanotransduction under the physiological condition is a matter of debate (Cheng et al, ; Deval & Lingueglia, ; Lingueglia, ), whereas ASIC3 is reported to be involved in proprioceptive mechanotransduction (Lin et al, ). In the present study, a selective blocker of ASIC3 administered to the naïve muscle via intramuscular injection did not alter the mechanical withdrawal threshold, indicating that ASIC3 played no role in the normal mechanical pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…ASIC3 is a sensor capable of detecting extracellular pH and metabolites in the muscle (Cheng et al, 2018;Deval et al, 2010;Deval & Lingueglia, 2015;Light et al, 2008;Molliver et al, 2005). In rats, the expression of ASIC3 is more abundant in small sensory neurons innervating the muscle than those innervating the skin (Fujii et al, 2008;Molliver et al, 2005).…”
Section: Asic3 From a Proton Sensor To A Mechanical Modulatormentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the experimental conditions tested to date may not have been appropriate for producing mechanosensitive currents from cells expressing Ppk channels. Similarly, ASICs in mammals, which respond to acid and have been implicated in mechanosensation in vivo, have not been shown to directly produce currents in cells by mechanical force. In this regard, Ppk1 and Ppk30 are similar to mammalian ASICs.…”
Section: Discussionmentioning
confidence: 99%
“…This alteration in metabolism produces lactic acid and H + , which are the by-products responsible for the decreased pH and increased acidity (Li et al, 2016). Acidsensing ion channels are cation channels belonging to the family of degenerin/epithelial sodium channels that are gated by H + (Cheng, Jiang, & Chen, 2018;Waldmann, Champigny, Bassilana, Heurteaux, & Lazdunski, 1997). These channels have dual functions of chemo-sensing and mechano-sensing (Cheng et al, 2018).…”
Section: Tehse and Taghibigloumentioning
confidence: 99%